Pelatihan Pengembangan Aplikasi berbasis Thunkable pada Anak Remaja di GKI Kasih Perumnas Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Citra Citra; Reva Reva (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This training activity on application development using the Thunkable platform was designed to enhance digital literacy, logical thinking skills, and strengthen the character of adolescents through a Project-Based Learning (PjBL) approach. In today’s digital age, digital literacy is an essential competency, and equipping young people with the ability to create meaningful technology empowers them to be not just users but also creators of impactful digital solutions. The training took place on May 17, 2025, at a member’s house from the GKI Kasih congregation in Perumnas, Sorong. It was attended by 20 participants aged between 12 and 17 years. The choice of a familiar and friendly setting was intended to create a comfortable and collaborative learning environment. The training materials were structured step-by-step, starting with an introduction to the Thunkable platform, user interface (UI) design, navigation logic development using visual block programming, and culminating in group presentations and reflections on the final projects. The project theme chosen for the training was "Prophets as Role Models," aimed at integrating spiritual values and character development into an educational digital application. Through this project, participants not only gained technical skills but also reflected on the moral and inspirational values of prophetic figures in the Christian faith. Evaluation results showed that the training had a significant positive impact. Participants demonstrated increased understanding of app development concepts, were able to explain their project workflows and features, and showed high levels of enthusiasm and creativity throughout the process. Furthermore, character values such as teamwork, responsibility, and a strong learning spirit were fostered. This initiative serves as a concrete example of how technology-based education can be effectively combined with character formation. It also provides a replicable training model for other communities, particularly for church-based youth development programs that aim to nurture digitally literate and morally grounded future generations.